2021
DOI: 10.3390/foods10092061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Automated Extraction Techniques for Volatile Analysis of Whole Milk Powder

Abstract: Volatile profiling of whole milk powder is valuable for obtaining information on product quality, adulteration, legislation, shelf life, and aroma. For routine analysis, automated solventless volatile extraction techniques are favored due their simplicity and versatility, however no single extraction technique can provide a complete volatile profile due to inherent chemical bias. This study was undertaken to compare and contrast the performance of headspace solid phase microextraction, thermal desorption, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Bendall et al ( 13 ) also found an odour-active lactone (γ-dodec-cis-6,cis-9-dienolactone) present in milk derived from a TMR diet but absent in cows on a pasture diet. However, it appears that the extraction method can also have a significant impact on the recovery of many lactones ( 20 , 21 ) and that HS-SPME is not very suitable for the extraction of lactones (dependent upon fibre type), an extraction technique widely used for VOC analysis in bovine milk ( 27 , 28 , 31 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bendall et al ( 13 ) also found an odour-active lactone (γ-dodec-cis-6,cis-9-dienolactone) present in milk derived from a TMR diet but absent in cows on a pasture diet. However, it appears that the extraction method can also have a significant impact on the recovery of many lactones ( 20 , 21 ) and that HS-SPME is not very suitable for the extraction of lactones (dependent upon fibre type), an extraction technique widely used for VOC analysis in bovine milk ( 27 , 28 , 31 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also identified butanoic acid in bovine milk (1,13,16,27,28) although abundances were not statistically different in raw or pasteurised milk from these diets. The choice of the extraction method and the GC column used is likely to have a significant effect on the recovery of butanoic acid, as the recovery of acids is greatly influenced by the polarity of the sorbent and GC column (21). γ-Hexalactone is a lactone, with a coconut, fruity, sweet aroma and a medium odour threshold (45), but was described in this study as having a barbeque, caramel, tobacco, toasted, toffee aroma (as the odour was so diverse, it is possible that coelution may have occurred with another odour-active VOC that was below the limits of MS detection).…”
Section: Aroma-active Volatiles In Raw Grs Milk By Odour Intensity An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially it was only available with PDMS but is now also available with PDMS/CWR, PDMS/DVB, and DVB/CWR/PDMS. Typical Hi‐Sorb applications include aromatics in coffee, lactones in milk, bacterial VOC in bodily fluids and esters in whisky [100], and whole milk powder [101], but no research has been carried out on meat to date.…”
Section: Sampling/extraction Methodsmentioning
confidence: 99%
“…We trapped the root volatiles from the headspace in a compartmentalized setup using two different sorbent materials: polydimethylsiloxane (PDMS) in silicon-based tubes and commercial coated probes (HiSorb TM ). These materials have been reported to be widely used for passive sampling of volatiles from soil and roots [ 16 , 17 , 18 ]. Combining these two trapping methods, we compared the root volatilome of the domesticated tomato Solanum lycopersicum cv Moneymaker with that of its wild relative Solanum pimpinellifolium under attack of the leaf herbivore insect Spodoptera exigua .…”
Section: Introductionmentioning
confidence: 99%